Protection of the Rights of Children in Conflict with the LawIn the Juvenile Criminal Justice System in Indonesia - Rahmawan Dianto; Martitah; Dewi Sulistianingsih (Universitas Negeri Semarang, 2025)
A child is someone who is not yet 18 years old, including a child who is still in the womb. Every child has the principle of basic rights, namely survival, non-discrimination, growth and development, and respect for participation. A child in conflict with the law is someone who is 12 years old, but not yet 18 years old who is suspected of committing a crime. Protection of the rights of children in conflict with the law needs to be carried out so that the child continues to receive their rights. This writing examines the basic rights of children for children in conflict with the law in Indonesia and the protection of the rights of children in conflict with the law in Indonesia. This writing uses a normative legal method, namely positive legal research, research on legal principles, clinical legal research, legal research examining legislation, and comparative legal research and synchronization of legislation. Handling of child cases is carried out based on the Juvenile Criminal Justice System so that the protection of the rights of children in conflict with the law in Indonesia can be implemented properly and children in conflict with the law continue to receive their rights in full. Keywords: Principles of children's rights; children in conflict with the law; child protection; reform of the Juvenile Criminal Justice System.